Polyvinyl alcohol (pva) / cellulose acetate (ca) based environmentally friendly hybrid filter production - ERTEK, DİCLE AYÇA; YÜKSEK, METİN (My University, 2022)
Abstract: In this study, the development of filters made of spunbond fabric coated with nanofiber surface was studied. With Covid 19, filters have gained importance in terms of human health. In this study, it is aimed to produce filters by using cellulose acetate and polyvinyl alcohol materials with the help of solution blowing method. The purpose of choosing polyvinyl alcohol (PVA) raw material is that it is not toxic and not polluting the environment, has high chemical stability, high abrasion resistance and low cost. Cellulose acetate (CA) material was chosen because it is a renewable, biodegradable, low-cost and high-quality fiber source that can be used in many manufacturing processes. These two materials were chosen in order to make the produced filter environmentally friendly and biodegradable. For the samples produced; tensile strength and FT-IR tests were carried out.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES; Hybrid Filter; Cellulose acetate (CA); Polyvinyl alcohol (PVA); Nanofiltration; Solution Blowing Method